(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2013)
Peucedanum grande has been found to be associated with the several therapeutic properties. In the current study, we have used P. grande as an ameliorating agent against nephrotoxic effects of Potassium dichromate. Potassium dichromate (K2Cr2O7) is a soluble hexavalent chromium compound that is extensively used in several industries. The rats were given pretreatment of P. grande orally at a dose of (60 and 120 mg/kg body weight) for five consecutive days 10 mg/kg b.wt was used as renal toxicant, and injected subcutaneously in the neck region in a volume of 1 ml/kg. The modulatory effects of P. grande on Potassium dichromate induced nephrotoxicity was investigated by assaying oxidative stress biomarkers, lipid peroxidation, serum kidney toxicity markers and by histopathological examination of kidney. P. grande pretreatment prevented deteriorative effects induced by Potassium dichromate through a protective mechanism that involved reduction of increased oxidative stress as well as by restoration of histopathological change against Potassium dichromate administration.